2022
DOI: 10.2147/ijwh.s356855
|View full text |Cite
|
Sign up to set email alerts
|

Length of Hospital Stay After Cesarean Delivery and Its Determinants Among Women in Eastern Sudan

Abstract: Background There is an increasing caesarean delivery (CD) rate globally. Length of hospital stay (LoS) is longer in CD compared with vaginal delivery. There are few published data on LoS following CD in Africa, including Sudan. We aimed to investigate LoS after CD in eastern Sudan and its associated risk factors. Methods A cross-sectional study was conducted at Gadarif hospital in eastern Sudan from May to December 2020. Sociodemographic, clinical and obstetrical data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The present study found maternal complications were an independent determinant of longer LOS following VD. The finding is consistent with Prior literature reports [ 29 , 34 ]. The provision of post-partum care is essential for mothers following childbirth, even more so for mothers who experience complications during labor.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study found maternal complications were an independent determinant of longer LOS following VD. The finding is consistent with Prior literature reports [ 29 , 34 ]. The provision of post-partum care is essential for mothers following childbirth, even more so for mothers who experience complications during labor.…”
Section: Discussionsupporting
confidence: 94%
“…Prior Reports have documented that LOS following CD has large variability (2.5–9.3 days) across different contexts [ 10 ]. Lower median LOS following CD has been reported in Sudan [ 29 ], Australia [ 30 ], and the US [ 25 , 31 ]. On the other hand, comparable LOS in mothers who delivered via CD has been reported in India [ 21 ], Malawi, and Ghana [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was however conducted in a surgical ward. The median length of hospital stay was the same as a study that conducted Eastern Sudan among mothers following cesarean delivery (10). The components of clerkship that were signi cantly associated with days of hospitalization include vital examination, abdominal examination, history of presenting complaint and treatment plan.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This risk is particularly relevant when considering the underdeveloped neonatal immune system, emphasizing the importance of meticulous adherence to proper aseptic procedures. [40][41][42] Neonates born from cesarean section also receive less skin-to-skin contact and a later initiation of breastfeeding. 43 Colostrum or the first milk contains high concentrations of immune components, including antibodies, immune cells, cytokines, lactoferrins and complements, which are essential for protection against infectious diseases.…”
Section: Discussionmentioning
confidence: 99%